(untitled) (Sains Humanika, 2015)
Technology such as gaming, animations, and interactive problem-solving have been adapted at learning platforms to help explain or illustrate complex concepts, and even make learning fun for the audience. However, such technologies are deployed in limited number of learning environments due to the lack of financial resources, expertise, change agents, and willingness of educational institutions to move beyond traditional practices. The Massive Open Online Course (MOOC) phenomenon, started three years ago, could address the above challenges, and create a great technological disruption in education. With millions in venture capital backing, MOOC providers have the expertise and money to incorporate the latest technologies into e-courses and revolutionize learning. But the economic model of MOOCs is still evolving. MOOC organizations such as edX, Coursera, Udacity, Udemy, and NovoEd have yet to figure out a financially viable model. At the current time, most MOOCs are free (or at nominal fees) to the students. Hence, one of our research questions in this paper is how would MOOCs generate sustainable revenue in a few years? Our second research question deals with how MOOC providers plan to facilitate learning and assessments (even with state-of-the-art technologies) for the thousands or tens of thousands of students per course. If partnerships with universities or colleges would be an economically feasible and manageable solution, then how would MOOC providers’ business model change strategically? We discussed a number of financial models on monetizing MOOC, and strategies for MOOC organizations to make MOOC more mainstream and accepted by academe and prospective employers.